Student’s Self-Regulated Learning in Online Class Design Based on Reflective Learning - Darmiany Darmiany; Siti Istiningsih; Iva Nurmawanti; Nurwahidah Nurwahidah; Mohammad Archi Mauldya (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explored the connection between Self-Regulated Learning (SRL) strategies and student learning outcomes, alongside detailing the SRL strategies students employ in reflective learning contexts. Conducted as a quantitative descriptive with 53 student participants, the research utilized correlation analysis to examine the interrelationships between various SRL strategies and employed a three-stage qualitative analysis process: data reduction, data presentation, and conclusion drawing. The findings reveal significant positive correlations among SRL strategies, notably between learning responsibility and environmental structuring (r = 0.706), memory strategy and goal setting (r = 0.717), and goal setting and self-evaluation (r = 0.722). The least positive correlation was found between self-evaluation and organizing (r = 0.437). Additional positive relationships were identified between memory strategy and perceived value (r = 0.668), goal setting and value (r = 0.762), self-evaluation and value (r = 0.669), seeking assistance and value (r = 0.763), environmental structuring and value (r = 0.825), learning responsibility and value (r = 0.795), and organizing and value (r = 0.645). Reflective learning stages—comprising the forethought phase, the performance phase as evidenced by students presenting their experiences, and the self-reflection phase during evaluation—highlight the intricate dynamics of students' SRL strategies. This study underscores the positive impact of SRL strategies on learning outcomes, offering insights into the effective application of reflective learning in educational settings.